ANALISIS PENERAPAN PENYUSUNAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK ETAP - Agus Andriyani Purnani Sari (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2016)
The financial statement is the primary means of communicating financial information to parties outside of the company, which contains the results of the accounting process that can be used as a means of communication between financial information and or activity of a company with the parties concerned with the information or corporate activity, In this case UD. Irawan Jaya Plastindo as entity that publishes general purpose financial statement for external users is expected to make a financial report in accordance with the standard, it is the standards of financial accounting entity without public accountability (SFA EWPA) standard reserved for SMEs. The purpose of this study is to investigate the compilation and presentation of financial statement by an entity's financial accounting standards without public accountability (SFA EWPA), This research uses descriptive quantitative research with the case study method. The results of this study indicate that UD. Irawan Jaya Plastindo SFA EWPA not apply in preparing its financial statements, it is due to limited knowledge possessed by the company and its human resources.